Rapid detection of bacterial meningitis using a point-of-care glucometer. (February 2019) - Rousseau, Geoffroy; Asmolov, Romain; Grammatico-Guillon, Leslie; Auvet, Adrien; Laribi, Said; Garot, Denis; Jouan, Youenn; Dequin, Pierre-François; Guillon, Antoine
Abstract : Background: In case of acute bacterial meningitis, a decision on the need for intensive care admission should be made within the first hour. The aim of this study was to assess the ability of a point-of-care glucometer to determine abnormal cerebrospinal fluid (CSF) glucose concentration at the bedside that contributes toward bacterial meningitis diagnosis. Methods: We carried out a prospective study and simultaneously measured the glucose concentrations in CSF and blood using a central laboratory and a point-of-care glucometer. We compared CSF/blood glucose ratios obtained at the bedside with a glucometer versus those obtained by the central laboratory. We determined the performance characteristics of the CSF/blood glucose ratio provided by a glucometer to detect bacterial infection in the CSF immediately after CSF sampling. Results: We screened 201 CSF collection procedures during the study period and included 172 samples for analysis. Acute bacterial meningitis was diagnosed in 17/172 (9.9%) of CSF samples. The median turnaround time for a point-of-care glucometer analysis was 5 (interquartile range 2–10) min versus 112 (interquartile range 86–154) min for the central laboratory ( P <0.0001). The optimal cut-off of the CSF/blood glucose ratio calculated from a bedside glucometer was 0.46, with a sensitivity of 94.1% (95% confidence interval: 71.3–99.9%), a specificity of 91% (95% confidence interval: 85.3–95%), and a positive likelihood ratio of 10. Conclusion: A glucometer accurately detects an abnormal CSF/blood glucose ratio immediately after the lumbar puncture. This cheap point-of-care method has the potential to speed up the diagnostic process of patients with bacterial meningitis.